Main risk factors of hypertension in workers of "Renato Guitart Rosell" Provincial Blood Bank - Niurka Aurora Ali Pérez; Jaime Fernando Reyes Ali; Norberto Ramos Labrada; Maiyenis Herrada Cuevas; Ricardo García Álvarez (Centro Provincial de Información de Ciencias Médicas, 2018)
A descriptive and cross-sectional study, aimed at determining the main risk factors of hypertension in 92 workers of "Renato Guitart Rosell" Provincial Blood Bank inSantiago de Cuba, was carried out from October, 2015 to May, 2016. It was found that 20.6 % of these workers suffered from the disease. Among the main risk factors, female sex, 41-50 age group, stage I of the disorder, history of hypertension, absence of physical exercises, stress, high consumption of salt, history of relatives with hypertension and obesity were the most outstanding. It was also detected that most of the patients didn't fulfil the treatment; therefore, some measures were required for the elimination and/or modification of the risk factors that allowed to improve the life quality and diminish the crises, which would contribute to the prevention and control of this disease.